Socio-economic Factors Affecting School Continuation Among the Underprivileged Students in Bangladesh - Taslima Ahmed; Md Sanaul Haque Mondal (Interdisciplinary Journal of Education, 2025)
This article examines the effects of socio-economic factors on school continuation among underprivileged students in Bangladesh when the cost of schooling remains constant. Researchers followed a cohort of students from first through eighth grade to identify socioeconomic factors related to students who completed eighth grade and those who dropped out before reaching 8th grade. The school covered all necessary student expenses, including tuition fees, textbooks, uniforms, light meals, and other related study materials. Data collection involved a semi-structured questionnaire from students who continued through eighth grade (n=66), and information for students who discontinued their education before eighth grade was extracted from the schools’ database (n=87). We analysed data using Fisher's exact test and binary logistic regression, with findings suggesting that, despite providing students with the cost of schooling, the retention rate remains lower (43.1%) than the dropout rate (56.9%). Various factors are responsible in this regard: the place of origin (OR: 4.84, 95% CI: 1.55-15.14), marital status (OR: 0.09, 95% CI: 0.01-0.90), mother’s education (OR: 2.80, 95% CI: 1.01-7.80), family income (OR: 10.70, 95% CI: 3.50-32.68), living with both parents (OR: 0.10, 95% CI: 0.02-0.49), among other factors. Findings suggest that even if schooling costs remain constant, other socio-economic factors influence the dropout rate of underprivileged students. These findings are crucial for policymakers to comprehend the nature of dropout among children from underprivileged backgrounds in Bangladesh and other developing countries.